Produção e consumo de café: uma análise do custo de oportunidade de produção de cafés especiais e convencionais - Gonçalves, Marcos Davi Barbosa (2019)
For more than 100 years, Brazil has been the leader in the world market as the largest producer of coffee and one of the largest exporters of coffee, and accounts for about a third of world production. It is notorious the role of this product in the Brazilian economy, being considered as an important product for the social and economic development of the country. The coffee production scenario is increasingly competitive internally, with around 300 thousand producers, occupying an area of 2 million hectares in approximately 1,900 Brazilian municipalities (MAPA, 2018). In international markets, the main competitor in terms of volume produced is Vietnam, a major producer of Robusta coffee, followed by Colombia, Indonesia and Ethiopia known for producing quality Arabica coffees. These five countries in 2017 accounted for 62.5% of world production (CONAB, 2017). Given this scenario, it is relevant to investigate the extent to which it is advantageous, from the perspective of the farmer, to produce large volumes without prioritizing quality. It is notable the increase in the number of consumers of so-called specialty coffees or gourmet coffees - differentiated coffees, classified as 'special' and which value for quality. This is a niche market that, according to the Brazilian Coffee Industry Association - ABIC (2018), has grown about 19% per year and reveals a new trend of national and international consumption. This fact has had repercussions in the field and it is noticed that many producers are exchanging the production of conventional coffees and betting on the excellence of the cultivation of special coffees, which can generate significant returns. Through the case study of a property in the municipality of Patrocínio / MG, the opportunity cost and the return of the producer in the transition from the conventional to the special coffee production were analyzed, considering a scenario of growth of the domestic consumption. The results indicate that the use of different management methods combined with investments in the pre and post-harvest and with a strict phytosanitary control result in a final product with great added value and that investments in the crop in order to improve the final quality of the coffee and frame as special, can generate a gain 64% higher than conventionally produced coffee. It is concluded, therefore, that special coffee demands much more care and cultural treatment than conventional coffee, in addition to the investments necessary for the adequacy of the crop. However, it is 10 noted that the return received at the time of sale in the property analyzed makes the investment attractive and economically viable.